2017
DOI: 10.1017/aog.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Meltwater runoff in a changing climate (1951–2099) at Chhota Shigri Glacier, Western Himalaya, Northern India

Abstract: ABSTRACT. Meltwater runoff in the catchment area containing Chhota Shigri glacier (Western Himalaya) is simulated for the period 1951-2099. The applied mass-balance model is forced by downscaled products from four regional climate models with different horizontal resolution. For the future climate scenarios we use high resolution time series of 5 km grid spacing, generated using the newly . Average annual runoff does not differ substantially between the two climate scenarios. However, for the years after 2040 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…Our decision to use dynamically downscaled reanalysis data as model forcing data rather than meteorological observations is based on a simple model experiment. We found that hydrologic simulations perform equivalent to other studies when using observations as input (Hegdahl et al, 2016;Li et al, 2015) yet significantly better when using dynamically downscaled reanalysis data (see supporting information for details; Diggle & Ribeiro, 2007;Engelhardt et al, 2017). Figure 2 introduces our methodology which provides a concurrent instantaneous RFS calculation for direct comparison with MODDRFS .…”
Section: Study Location and Meteorological Forcingmentioning
confidence: 82%
“…Our decision to use dynamically downscaled reanalysis data as model forcing data rather than meteorological observations is based on a simple model experiment. We found that hydrologic simulations perform equivalent to other studies when using observations as input (Hegdahl et al, 2016;Li et al, 2015) yet significantly better when using dynamically downscaled reanalysis data (see supporting information for details; Diggle & Ribeiro, 2007;Engelhardt et al, 2017). Figure 2 introduces our methodology which provides a concurrent instantaneous RFS calculation for direct comparison with MODDRFS .…”
Section: Study Location and Meteorological Forcingmentioning
confidence: 82%
“…Since peaks represented by only one grid point increase the wave energy in the high frequency part of the spectrum, leading to unphysical atmospheric perturbations, the topography was smoothed by a 3 × 3 moving window algorithm (Guo and Chen, 1994, p.34). A similar type of smoothing, which is common when using the weather research and forecasting pre-processing system, was performed in previous studies employing ICAR (Gutmann et al, 2016;Engelhardt et al, 2017).…”
Section: Digital Elevation Modelmentioning
confidence: 99%
“…Gutmann et al (2016) used the North American Regional Reanalysis (NARR), which has a 32 km grid spacing (Mesinger et al, 2006). Engelhardt et al (2017) use output from the Norwegian Earth System Model (NorESM), downscaled to a grid spacing of 25 km by the regional climate model REMO, as ICAR input for a simulation period from 2006 to 2099. In this study, ERAI are preferred over regional reanalysis data sets because of their global availability and thus more widespread applicability.…”
Section: Forcing Data and Referencementioning
confidence: 99%
See 1 more Smart Citation
“…At the time of writing, ICAR has been evaluated in an idealized hill experiment, as well as by comparing monthly precipitation fields generated by ICAR for Colorado, USA, with WRF output and an observation-based gridded data set (Gutmann et al, 2016). Furthermore, ICAR was employed to generate downscaled atmospheric fields as input for a glacier mass balance model to simulate meltwater runoff in the western Himalayas (Engelhardt et al, 2017). Recently Bernhardt et al (2018) applied ICAR to investigate differences in precipitation patterns and amounts for a domain in the European Alps, emerging from the choice of the microphysics scheme and associated parameters.…”
Section: Introductionmentioning
confidence: 99%